2014
DOI: 10.1111/jir.12176
|View full text |Cite
|
Sign up to set email alerts
|

Fine motor and self‐care milestones for individuals with Down syndrome using a Retrospective Chart Review

Abstract: Age ranges for the mastery of fine motor developmental milestones for early and representative achievement were developed based upon descriptive analysis of cross-sectional retrospective clinical chart reviews. That the age range for mastering fine motor and self-care skills broadens as children with DS get older is in agreement with what is identified in the DS behavioural phenotype with regard to variable motor skills overall. These fine motor and self-care developmental milestone markers contribute to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 14 publications
0
43
0
2
Order By: Relevance
“…Down syndrome (DS) is the most common chromosomal abnormality [123]; it occurs in 1 per 691 babies, caused by the trisomy of chromosome 21 and associated with a characteristic phenotype in terms of physical appearance as well as with medical problems such as metabolic disorders, tissue dysmorphism, congenital heart disease (CHD), and thyroid dysfunction [4]. Typically, over-expression of the chromosome results in a decrease of the overall number of neurons in the central nervous system, a delay of myelination, and dysregulation of cell cycles that lead to overproduction of protein precursors and subsequently cause neurotransmission abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Down syndrome (DS) is the most common chromosomal abnormality [123]; it occurs in 1 per 691 babies, caused by the trisomy of chromosome 21 and associated with a characteristic phenotype in terms of physical appearance as well as with medical problems such as metabolic disorders, tissue dysmorphism, congenital heart disease (CHD), and thyroid dysfunction [4]. Typically, over-expression of the chromosome results in a decrease of the overall number of neurons in the central nervous system, a delay of myelination, and dysregulation of cell cycles that lead to overproduction of protein precursors and subsequently cause neurotransmission abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies about motor development in children with DS mainly focused on gross motor skills [78910], fine motor functions [1111213], and postural control [1415]. A few investigations have revealed that DS-afflicted children are delayed in vocabulary and cognitive development [16].…”
Section: Introductionmentioning
confidence: 99%
“…Also with pathologies treatments for these children, as in case of acute leukemia [23] and congenital cardiac abnormalities [24] Such studies, specific for clinical health conditions of children with Down syndrome, demonstrate that manual dexterity evaluation and fine motor skills also constitute parameters to assess these children health status. Those studies also enable the evolution follow-up of many treatments for common diseases associated with genetic conditions, such as Down syndrome [28].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 5 articles [26][27][28][29] present instruments aiming to evaluate intelligence, balance, language, bio psychosocial and visual perception; but all of them include some fine motor assessment skills in their study, as BOT-2, a Motor Proficiency Test used by Berg et al [22], aiming to measure fine motor skills of children and adolescents.…”
Section: -Effect Of Congenital Heart Malformations Upon Language Devmentioning
confidence: 99%
“…A research for adults with Down's syndrome included assisted and voluntary exercise with music that could improve fine manual dexterity (Chen, Ringenbach, & Albert, 2014). However, more consideration should be given to the developmental milestone of children with Down's syndrome (Frank & Esbensen, 2015). For these reasons, this study was interested in designing an intervention program and researching effectiveness of the fine motor activities program in order to promote fine motor skills, including bilateral hand coordination, hand prehension, manual dexterity, in-hand manipulation, and hand muscle strength in a case study of Down's syndrome.…”
Section: Introduction To the Problemmentioning
confidence: 99%